Evidence of alternative reproduction by drifting workers in the Japanese paper wasp, Polistes rothneyi Cameron, 1900 (Hymenoptera: Vespidae). Issue 2 (22nd December 2020) - Nishimura, Masakazu; Ono, Masato
Abstract: Intercolony drifting of the Japanese paper wasp, Polistes rothneyi Cameron, was observed using individual color marking of workers. No genetic relatedness was found by using microsatellite markers between drifting workers and the recipient colony. Genetic analysis of brood in the recipient colony revealed reproduction by non‐kin drifting worker(s) in the queenless host colony. The non‐kin broods were raised like broods of the recipient colony until the genetic analysis. This study is the first evidence of male production by non‐kin workers in temperate eusocial wasps. This natural event would compensate for fitness loss as an alternative reproductive strategy evolved under predation and climatic pressures, and is also discussed from the viewpoint of mutual help. Abstract : Intercolony drifting of Japanese paper wasp, Polistes rothneyi, was observed using individual color marking of workers.Genetic analysis of brood in the recipient colony revealed reproduction by non‐kin drifting workers. Although drifting of hymenopteran workers is known, this study is the first evidence in temperate eusocial wasps of male production by non‐kin workers.